Análise da atividade dos técnicos em enfermagem do SAMU - Felix, Yana Thamires Mendes (2015)
The present study investigated the activity of SAMU's nursing technicians, since these professionals perform activities with the time as a crucial variable, added the requirement of a collective work to fulfill it's mission. From a theoretical point of view, two approaches anchor this dissertation: the Psychodynamics of work and the Ergonomics. The sample consists of 30 participants and selected by convenience. To collect data, we used semi-structured interviews, associated with a indirect technique to analyze the activity called "Instructions to the double". To the treatment of the data, we used the tematic content analysis. Three main categories were identified: "Trajectory and training", which provided us with a profile of the path taken by the workers to join SAMU; "Real work", relative to the caracterization of typical and atypical working days; and finally, "Pleasure and Suffering at work." We observed that cooperation is a key concept for the proper functioning of the SAMU and the quality of work done by these professionals. It was also possible to see that there is a profound identification with the chosen profession, expressed in the motivation into their professional exercises and in the feeling of self-realization present in their speeches. However, there are sources of suffering at work, such as the lack of recognition, poor working conditions, the weakness of employment contracts, the absence of basic labor rights, low wages, among others. To deal with such circumstances, these professionals use strategies involving their skills and defensive strategies, which enable the maintenance of psychic equilibrium. We hope with dissertation results, to contribute to the production of knowledge on this category of workers, their health and the work they do in the SAMU.